Psoriasis in pregnancy: case series and literature review of data concerning exposure during pregnancy to ustekinumab. (2nd January 2019) - Galluzzo, Marco; D'Adamio, Simone; Bianchi, Luca; Talamonti, Marina
Abstract: Psoriasis tends to improve for approximately half of patients during pregnancy, but an equal number of patients report no change or worsening during this period, when lots of medications, like biologics, are not indicated. The aim of our study was to review data of patient that had been pregnant during ustekinumab treatment, analyzing data of our data set between September 2010 and February 2018. We found data of three patients that had been pregnant during ustekinumab treatment. All three patients successfully completed the pregnancy without complications. One of the three patients was pregnant even twice during treatment with ustekinumab, with also a successful birth of two perfectly healthy twins. Biologic agents approved for the treatment of moderate-to-severe psoriasis are currently classified as pregnancy category B, even if, particularly for ustekinumab, there are several case reports regarding exposure during pregnancy in humans related to a healthy pregnancy, both for women and children. Although further studies are required to find real indication of biological treatment in pregnant patients, according to our and to the reviewed experience, ustekinumab does not interfere with gestation.